Підстави визнання шлюбного договору недійсним за цивільним та сімейним законодавством України - Хобор, Р.; Khobor, R. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто як загальні, так і спеціальні підстави визнання шлюбного договору недійсним. Обґрунтовано можливість конвалідації шлюбного договору щодо якого недотримана вимога про його нотаріальне посвідчення. Встановлено, що передбачене ч. 1 ст. 203 ЦК України поняття «невідповідність актам цивільного законодавства» включає в себе неможливість регулювання шлюбним договором особистих немайнових прав і обов’язків, неможливість передбачення невигідних для одного з подружжя умов, неможливість врегулювання у шлюбному договорі відносин з передання у власність одному з подружжя нерухомого майна, права на яке підлягає державній реєстрації. Встановлено доцільність виключення ч. 5 ст. 93 СК України. The article describes both general and specific reasons allowing to recognize marriage contract (prenuptial agreement) invalid. The specific conditions, the violation of which will serve the basis for the recognition of the prenuptial agreement invalid, include the following items: 1) violation of the notarial form of the contract; 2) improper subject structure; 3) decrease in children's rights established by the Family Code of Ukraine; 4) the inclusion of the issues that put one of the spouses into an extremely unfavorable financial situation or concluding the marriage contract under the influence of heavy circumstances; 5) signing of the contract under the influence of fraud or violence; 6) an error of one of the parties to the contract; 7) violation of the law provisions by the marriage contract. The article highlights the possibility of the marriage contract convalidation concluded with violation of the requirements for notarial certification. The author proves the expediency of exceptions in Part 5, Art. 93 of the Family Code of Ukraine, as it significantly reduces the scope of the contractual freedoms of the parties of the prenuptial agreement, and substantiates the possibility of transfering ownership of immovable property to one of the spouses in accordance with the marriage contract, in case this right is the subject to state registration.
Grounds for Recognition of the Prenuptial Agreement Invalid in the Civil and Family Legislation of Ukraine
Keywords: шлюбний договір; подружжя; правочин; недійсність; правові наслідки; нотаріальна форма; двостороння реституція; prenuptial agreement; spouse; deal; invalidity; legal implications; notarial form; doublesided restitution